Implications of European Union recast Renewable Energy Directive sustainability criteria for renewable heat and transport: Case study of willow biomethane in Ireland. (October 2021) - Long, A.; Bose, A.; O'Shea, R.; Monaghan, R.; Murphy, J.D.
Abstract: The 2018 recast European Renewable Energy Directive (RED recast) sets emissions savings criteria for renewable fuels. This paper assesses the life-cycle emissions from gasification methanation of willow to produce renewable biomethane in order to compare the heat and transport 2026 sustainability criteria in the RED recast. The criteria are more stringent for use of the fuel as heat, with both a higher specified emissions savings criteria (80% versus 65% for transport) and a lower Fossil Fuel Comparator (80 g CO2 MJ −1 versus 94 CO2 MJ −1 for transport). Scenarios tested were based on both the RED recast and the IPCC (Intergovernmental Panel on Climate Change) Global Warming Potential (GWP) values. Agro-chemical input data from Teagasc (the Irish Agriculture and Food Development Authority) was used for both mineral and organic fertilisers. Previous land use was shown to have a significant impact on the results of the analysis. Overall, 24 scenarios were tested. Converting land from grassland for cultivation of willow results in greater emissions when compared to conversion from arable land. The gasification methanation pathway was found to meet emissions savings criteria for transport in most cases, and for heat when converting from arable land only. The highest emission saving of 97% was achieved through conversion from arable land for the transport end use. Highlights: Willow biomethane meets sustainability criteria in the RED recast for transport. Converting from grassland as opposed to arable land results in higher emissions. Willow biomethane from grassland does not meet sustainability criteria for heat.